Multi-scale radiative-transfer model of the protoplanetary disc DoAr 44 - Souza de Joode, Marco; Brož, Miroslav (Astronomy and astrophysics, 2025)
Aims: Our aim was to construct a comprehensive global multi-scale kinematic equilibrium radiative-transfer model for the pretransitional disc of DoAr 44 (Haro 1-16, V2062 Oph) in the Ophiuchus star-forming region. This model integrates diverse observational datasets to describe the system, spanning from the accretion region to the outer disc. Methods: Our analysis utilised a large set of observational data, including ALMA continuum complex visibilities, VLTI/GRAVITY continuum squared visibilities, closure phases, and triple products, as well as VLT/UVES and VLT/X-shooter Hα spectra. Additionally, we incorporated absolute flux measurements from ground-based optical observatories, Spitzer, IRAS, the Submillimeter Array, the IRAM, or the ATCA radio telescopes. These datasets were used to constrain the structure and kinematics of the object through radiative-transfer modelling. Results: Our model reveals that the spectral line profiles are best explained by an optically thin spherical inflow or outflow within the co-rotation radius of the star, exhibiting velocities exceeding 380 km/s. The VLTI near-infrared interferometric observations are consistent with an inner disc extending from 0.1 to 0.2 au. The ALMA sub-millimetre observations indicate a dust ring located between 36 and 56 au, probably related to the CO2 condensation line. The global density and temperature profiles derived from our model provide insight into an intermediate disc, located in the terrestrial planet-forming zone, which has not yet been spatially resolved.
Gesehen am 26.01.2026